Pengaruh Pemberian Kafein Terhadap Kebugaran Jasmani - Nofal, Ach; Syahab, Afaf Achmad; Yono, Topo; Apriliyanto, Rizki (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
The purpose of this study was to determine how caffeine affects students' physical fitness levels. Using a single group in an experiment Pre-test and post-test design was used on ten students of SMA Muhammadiyah 3 Jember, aged 15 to 17 years. There was no control group. The tools used to measure physical fitness used valid and standardized tests (TKSI), including Hand Eye Coordination test, Vertical Jump test, T test, Hand Touch Reaction test, Dipping test, Beep test. The sample received treatment in the form of 64 mg of caffeine, or one sip of espresso as much as 30 ml. Using the Paired sample t-test in this study. The findings of the study showed a statistically significant increase in all measures of Physical Fitness in students who took caffeine treatment (Post-test) compared to their baseline physical fitness (Pre-test). Conclusion, between the Pre-test and Post-test data was indicated by the Paired Sample t-test statistical test value, which showed a sig value (2-tailed) of 0.00 less than 0.05. Therefore, we can assume that children who use caffeine have a higher level of physical fitness. Keywords: caffeine, physical fitness, students